Analysis of Mangrove Vegetation in Lohgung Village, Brondong Sub-District, Lamongan Regency - Saad, Moch; Hasyim, Moch. Khafid (Universitas Airlangga, 2024)
Mangroves are vegetation that grows in muddy areas in tidal areas, coastal areas , and river estuaries. Mangrove forests have an ecological function as providing food for marine biota, preventing tidal waves and tsunamis, preventing sea water intrusion, preventing coastal erosion and absorbing waste. This research aims to determine the species and Importance Value Index in the mangrove area of Lohgung Village, Brondong District, Lamongan Regency, which included Relative Density (KR), Relative Frequency (FR), and Relative Dominance (DR). This research was carried out in Lohgung Village, Brondong District, Lamongan Regency from May to June 2023. The method used in sampling used a combination of the line method (line transect) and the plot line method (quadrant transect). The results showed that the types of vegetation found in Lohgung Village, Brondong District, Lamongan Regency consisted of 8 species from 5 different families, namely Sonneratia alba, Rhizophora apiculata, Rhizophora mucronata, Bruguiera gymnorrhiza, Ceriops tagal, Lumnitzera racemosa, Excoecaria agallocha L., and Xylocarpus moluccensis. The results of calculating the values of Density (K), Relative Density (KR), Frequency (F), Relative Frequency (FR), Dominance (D), Relative Dominance (DR), and Importance Value Index (IVI) in all categories, trees, saplings and seedlings showed that the highest value that dominated was Rhizophora mucronata with an IVI value of 102.08%, 68.73% for saplings and 75.40% for seedlings.